Clinical Practice Guidelines for Transfusion of Patients in Critical Condition. - Rafael Alejandro Gómez Baute; Diosdania Alfonso Falcón; Liermis Dita Salabert; Luciano Núñez Almoguea. (Medisur)
Clinical Practice Guidelines for Transfusion of Patients in Critical Condition. We stress transfusion criteria (blood cells, platelets, granulocyte concentrations, plasma and cryoprecipitate), doses, diagnosis and treatment of post-transfusion reactions. It includes assessment guidelines focused on the most important aspects to be accomplished.